Pragmatisme terhadap Pola Pertemanan IAIN Syekh Nurjati Cirebon Pasca Kuliah Daring - Raihan Athaya Mustafa; Indra Gunawan; Muhammad Ikhsan Ghofur; Gumilar Irfanullah; Lukman Zen (Gunung Djati Conference Series, 2023)
This study aims to collect data that rationalizes the reasons for pragmatism in friendship patterns at IAIN Syekh Nurjati Cirebon after college, daring with field data on senior students in today's reality. This study used a qualitative method by applying open interview techniques to senior students. The primary source is the result of a literature study related to the notion of pragmatism through online journals. The results and discussion show that some students recognize friendship because of benefits or interests. In other words, pragmatism has been embraced by most students. This is reasonable, because the concept of using philosophy is actually a way of perceiving, thinking, and acting that is honorably experienced by every human being. Some students seem to dissect in advance what is the advantage or benefit for them, unlike the pragmatism developed by John Dewey. This research resulted in the conclusion that pragmatism towards reality is quite massively carried out by various groups, especially students of IAIN Syekh Nurjati Cirebon, regardless of whether pragmatism is realized or not.